Care about climate? Animal nutrition can make the difference - International Livestock Research Institute; Land O'Lakes Venture37 (International Livestock Research Institute, 2021)
ILRI-Venture 37 webinar on care about livestock and livelihoods: Care about climate? Animal nutrition can make the difference. This film was recorded 30 November 2021.